You are here:

Algebra/Expert Profile


On Vacation
returns 10/24/2016

Any questions on High School Algebra, College Algebra, Abstract Algebra. I can help with word problems, solving equations, trigonometry, inequalities, Gaussian Elimination, Linear Algebra, groups, fields, you name it!

Experience in the area

Ph.D. in Mathematics, specialist in Algebra. I have taught High School students and college students at three state universities.


Mathematical Association of America. American Mathematical Society.


Regular contributions to the problems section of the American Mathematical Monthly journal.


B.S., M.S., Ph.D.

This expert accepts donations:      

Average Ratings

Recent Reviews from Users

Read More Comments

    K = Knowledgeability    C = Clarity of Response    P = Politeness
JohnnyX09/10/16101010Thanks for ya enormous amount of help!
Michael03/31/16101010Thank you. I really struggled with this .....
Jim12/21/15101010Thanks! Once again, what seemed insoluble becomes .....
Muhammad Ali11/28/1510 

Recent Answers from Socrates

2016-08-09 A question about proofs in college algebra:

The flaw is in the hidden assumption that the least such n is 3 or greater. In fact , the least such n is n = 2    If you try to carry out the argument with only two elements in S , Ti and Tj won't have

2015-11-27 logarithm base 2:

You can't give an exact value for   log2 (1,000,000) using decimals or fractions because it's an irrational number.  You can use the rules for logarithms to simplify it and then use a calculator.     1

2015-03-12 Mathematics:

You need the square roots of 3-2i and -2+i.    I will find the roots of 3-2i, then leave the roots of -2+i to you.      (a+bi) = 3-2i    a - b + 2abi = 3-2i    a - b = 3    2ab = -2      b = -1/a

2014-05-27 Word_problem:

The sum of their ages is equal to twice the difference if their ages    p + q = 2(p-q)    The product of their ages is 675    pq = 675    Solve the two equations :    p + q = 2(p-q)    pq = 675      Simplify

2014-01-30 equation:

x + y + z = 1    (x + y + z)^2 = 1    x^2 + y^2 +z^2 + 2xy + 2xz + 2yz = 1    35 + 2xy +2xz + 2yz = 1    2xy +2xz + 2yz = -34    xy + xz + yz = -17      -17 = (1)(xy + xz + yz ) = (x + y + z)(xy + xz +


Ask A Question


All Answers

Answers by Expert:

Ask Experts


©2016 All rights reserved.